Quantum transport in carbon nanotubes covalently functionalized with magnetic molecules. Issue 12 (14th July 2016) - Schnee, Michael; Besson, Claire; Frielinghaus, Robert; Lurz, Christian; Kögerler, Paul; Schneider, Claus M.; Meyer, Carola
Abstract : We report on quantum transport measurements of a carbon nanotube (CNT) quantum dot that is functionalized with magnetic Mn4 complexes. The coupling between the spin‐5/2 Mn II ions within each Mn4 complex is predominantly antiferromagnetic. Coulomb diamond measurements at T = 4 K reveal that the covalent attachment of the complexes to the CNT framework has only little influence on the carbon nanotube quantum dot. Surprisingly, a strong increase of noise is observed upon cooling the sample to T = 30 mK. Time traces of the current taken at a diamond edge reveal a random telegraph signal. We attribute this to fluctuations of molecular spin states of the attached Mn4 complexes.